Severe loss of mechanical efficiency in COVID‐19 patients. Issue 4 (8th June 2021) - Pleguezuelos, Eulogio; Del Carmen, Amin; Llorensi, Gemma; Carcole, Jessica; Casarramona, Paula; Moreno, Eva; Ortega, Pilar; Serra‐Prat, Mateo; Palomera, Elisabet; Miravitlles, Marc M.; Yebenes, Joan Carles; Boixeda, Ramón; et al.
Abstract: Background: There is limited information about the impact of coronavirus disease (COVID‐19) on the muscular dysfunction, despite the generalized weakness and fatigue that patients report after overcoming the acute phase of the infection. This study aimed to detect impaired muscle efficiency by evaluating delta efficiency (DE) in patients with COVID‐19 compared with subjects with chronic obstructive pulmonary disease (COPD), ischaemic heart disease (IHD), and control group (CG). Methods: A total of 60 participants were assigned to four experimental groups: COVID‐19, COPD, IHD, and CG ( n = 15 each group). Incremental exercise tests in a cycle ergometer were performed to obtain peak oxygen uptake (VO2 peak). DE was obtained from the end of the first workload to the power output where the respiratory exchange ratio was 1. Results: A lower DE was detected in patients with COVID‐19 and COPD compared with those in CG ( P ≤ 0.033). However, no significant differences were observed among the experimental groups with diseases ( P > 0.05). Lower VO2 peak, peak ventilation, peak power output, and total exercise time were observed in the groups with diseases than in the CG ( P < 0.05). A higher VO2, ventilation, and power output were detected in the CG compared with those in the groups with diseases at the first and second ventilatory threshold ( P < 0.05). A higher power output was detected in the IHD group compared with those in the COVID‐19 and COPD groups ( P < 0.05) at the first and second ventilatory thresholds and when the respiratory exchange ratio was 1. A significant correlation ( P < 0.001) was found between the VO2 peak and DE and between the peak power output and DE ( P < 0.001). Conclusions: Patients with COVID‐19 showed marked mechanical inefficiency similar to that observed in COPD and IHD patients. Patients with COVID‐19 and COPD showed a significant decrease in power output compared to IHD during pedalling despite having similar response in VO2 at each intensity. Resistance training should be considered during the early phase of rehabilitation.